2021
DOI: 10.46234/ccdcw2021.130
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the COVID-19 Epidemic and Acceptance of Vaccination Among Healthcare Workers Prior to Vaccine Licensure — Beijing Municipality, China, May–July 2020

Abstract: What is already known about this topic?The coronavirus disease 2019 (COVID-19) vaccine development has been progressing, but acceptance of the new vaccines by healthcare workers (HCWs) was not well known prior to approval of COVID-19 vaccines in China. What is added by this report?This study found that before vaccine approval, Beijing HCWs expressed moderate willingness to get vaccinated. Factors positively influencing willingness included free vaccination and belief that the vaccine had been fully evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This is consistent with the results of previous studies. For example, people with underlying diseases were generally less willing to be vaccinated [25][26][27][28][29][30][31][32] as they were more likely to refuse to be vaccinated due to worrying that the vaccination would aggravate their underlying diseases. This was more likely for women who were pregnant or preparing for pregnancy to refuse vaccinations, studies showed that they may hesitate to uptake the vaccine [33,34] due to the concerns about vaccine safety that large sample studies on the safety of vaccines in this group were invalid [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of previous studies. For example, people with underlying diseases were generally less willing to be vaccinated [25][26][27][28][29][30][31][32] as they were more likely to refuse to be vaccinated due to worrying that the vaccination would aggravate their underlying diseases. This was more likely for women who were pregnant or preparing for pregnancy to refuse vaccinations, studies showed that they may hesitate to uptake the vaccine [33,34] due to the concerns about vaccine safety that large sample studies on the safety of vaccines in this group were invalid [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that vaccine hesitancy caused by misinformation, pre-existing medical conditions, mistrust towards medical institutions and governments, concerns for vaccine efficacy, fear of vaccine adverse effects and respondents' sociodemographic characteristics were the main reasons behind vaccination reluctance [29][30][31][32][33]. Other studies identified healthcare workers, nurses, college students and parents with children under 18 as specific groups requiring targeted provaccine communication to address vaccine hesitancy [16,31,[34][35][36][37][38][39][40][41][42][43][44][45][46]. Health belief models related Chinese vaccine hesitancy to individual cognition factors, such as perceived benefits, perceived risks and perceived barriers [33,37].…”
Section: Introductionmentioning
confidence: 99%